Nomenclatural and distributional notes on Pecluma paradiseae (Polypodiaceae: Polypodioideae): typification of the name and its presence in Argentina - Lehn, Carlos Rodrigo; Arana, Marcelo D.; Bianchini, Edmilson (Phytotaxa, 2018)
The genus Pecluma M. G. Price (1983: 109) comprises terrestrial, epiphytic or epilithic ferns, usually medium-sized. Currently, 40 species belonging to the genus are recognized, occurring in the warmer parts of the New World, from Florida to northern Argentina, with a unique set of characteristics: short-creeping, non-glaucous rhizomes with basifixed, pseudopeltate to peltate scales, often terete stipes and rachises, pinnatisect or pectinate-pinnatifid blades with numerous linear or narrowly deltate segments, and sterile lamina parts with acicular cells beside multicellular branched or unbranched glandular hairs (Price 1983; Hennipman et al. 1990; Moran 1995, Assis et al. 2016).